Gothic Style in the French Theory of Architecture and Graphics of the Second Half of the16th–17th Centuries - Arutyunyan, Julia I. (Actual Problems of Theory and History of Art, 2016)
The French theoretical thought and architectural drawings of the second half of the 16th– 18th centuries were influenced by Gothic heritage. In the treatises by Philibert Delorme, the features of the ribbed vault, along with pointed and keel arches were discussed, and the “French order” was mentioned. François Blondel notes harmonic proportions of the façade of the Milan Cathedral. Jacques Androuet Ducerceau develops the idea of combining Baroque and late Gothic details in the decoration of buildings; in the treatise The most excellent buildings of France, he reproduces architectural structures of the Late Middle Ages. In the creative work of Etienne Martelange, sketches depicting medieval churches are fundamentally important. Abraham Bosse uses Gothic motifs in his etchings. André Félibien reproduces the construction associated with the French crown. Bernard de Montfaucon in The Monuments of the French monarchy embodied the sculpture of the facades of Gothic churches. Seroux d’Agincourt publishes an essay on history of art meticulously reproducing the works of medieval art. French architectural graphics of the 16th–18th centuries are like a path from Renaissance treatises using Gothic details through the practical study of scientific illustrations, which generally reflects the attitude toward Gothic reminiscences and the main vector of developing graphical reproductions of buildings of this period.